The Effect of Digital Marketing and Personal Selling on Consumer Purchase Decisions in Beauty Products - Ade Kurniawati; Junita Lubis; M. Ali Al-Ihsan (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
MS.GLOW beauty products is a business engaged in the beauty or skincare section, in marketing MS.GLOW products using digital marketing and personal selling to make consumer purchasing decisions. And the purpose of this research is: (1) to find out whether digital marketing influences purchasing decisions; (2) to find out how personal selling influences purchasing decisions; (3) to find out whether digital marketing has a simultaneous effect on purchasing decisions. In this study, the quantitative correlation method was used to analyze the numbers. The population of this study is all consumers who buy MS.GLOW products at Cut Rafa Aek Nabara stores and the sample in this study is representative of the population in this study as many as 60 people. The sampling method in this study used saturated sampling techniques. The analysis technique used is a statistical test. The results of the study explain that digital marketing and personal selling variables influence consumer purchasing decisions which show that the coefficient value Y = 0.909 + 0.836X with a significant 0.000 is smaller than 0.06 and statistical calculations in the summary model with an R Square value of 0.732 means digital marketing and personal selling influence on purchasing decisions.